2019
DOI: 10.1128/iai.00347-19
|View full text |Cite
|
Sign up to set email alerts
|

Association of TRAF1/C5 Locus Polymorphisms with Epilepsy and Clinical Traits in Mexican Patients with Neurocysticercosis

Abstract: Neurocysticercosis is caused by the establishment of Taenia solium cysts in the central nervous system. Murine cysticercosis by Taenia crassiceps is a useful model of cysticercosis in which the complement component 5 (C5) has been linked to infection resistance/permissiveness. This work aimed to study the possible relevance for human neurocysticercosis of single nucleotide polymorphisms (SNPs) in the C5-TRAF1 region (rs17611 C/T, rs992670 G/A, rs25681 G/A, rs10818488 A/G, and rs3761847 G/A) in a Mexican popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The role of the complement system in NCC is not yet fully understood. A recent investigation has associated the complement component C5 haplotype CAA with extraparenchymal infection [23]. Furthermore, previous investigations suggest that the complement system may be involved in the activity of antibodies generated during NCC [22,24].…”
Section: Humoral Immune Responses In Nccmentioning
confidence: 99%
“…The role of the complement system in NCC is not yet fully understood. A recent investigation has associated the complement component C5 haplotype CAA with extraparenchymal infection [23]. Furthermore, previous investigations suggest that the complement system may be involved in the activity of antibodies generated during NCC [22,24].…”
Section: Humoral Immune Responses In Nccmentioning
confidence: 99%
“…374 The evidence is not limited to TLRs, and includes adaptor proteins as well. Villegas et al 375 showed a link between TRAF1/C5 Locus polymorphisms with seizures and clinical features in mexican cases with neurocysticercosis. Also, relation of the gene polymorphisms in pre-miRNAs were investigated along with risk of childhood epilepsy in a Chinese subpopulation.…”
Section: Lithiummentioning
confidence: 99%